A novel mutation A212T in chloroplast Protoporphyrinogen oxidase (PPO1) confers resistance to PPO inhibitor Oxadiazon in Eleusine indica. Issue 5 (23rd January 2020) - Bi, Bo; Wang, Qiang; Coleman, Jeffrey J; Porri, Aimone; Peppers, John M; Patel, Jinesh D; Betz, Michael; Lerchl, Jens; McElroy, J. Scott
Abstract: BACKGROUND: Protoporphyrinogen oxidase (PPO) with two isoforms, chloroplast‐targeted ( PPO1 ) and mitochondrial‐targeted ( PPO2 ), catalyzes a step in the biosynthesis of chlorophyll and heme. PPO1 and PPO2 are herbicide target sites of PPO‐inhibiting herbicides. Target‐site mutations conferring resistance to PPO inhibitors have all thus far been in PPO2. Oxadiazon is a unique PPO inhibitor utilized for preemergence Eleusine indica control. In this research, we evaluated the response of two previously confirmed oxadiazon‐resistant and susceptible E. indica biotypes to other PPO inhibitors and identified the resistance mechanism in two oxadiazon‐resistant E. indica biotypes. RESULTS: Two E. indica biotypes were resistant to oxadiazon, but not to other structurally unrelated PPO inhibitors, such as lactofen, flumioxazin and sulfentrazone. A novel mutation A212T was identified in the chloroplast‐targeted PPO1, conferring resistance to oxadiazon in a heterologous expression system. Computational structural modeling provided a mechanistic explanation for reduced herbicide binding to the variant protein: the presence of a methyl group of threonine 212 changes the PPO1 active site and produces repulsive electrostatic interactions that repel oxadiazon from the binding pocket. CONCLUSION: The novel A212T mutation in PPO1 conferring resistance specifically to PPO inhibitor oxadiazon was characterized. This is the first evidence of the direct role of PPO1 in the PPO mode of action, and the first evidence of evolved resistance in PPO1 . © 2019 Society of Chemical Industry Abstract : A novel mutation A212T in chloroplast PPO1 confers resistance to PPO inhibitor oxadiazon, but not to other PPO inhibitors in Eleusine indica . This is a report of field‐resistance in PPO1.